Promoting Well-Being in Old Age: The Psychological Benefits of Two Training Programs of Adapted Physical Activity - Delle Fave, Antonella; Bassi, Marta; Boccaletti, Elena S.; Roncaglione, Carlotta; Bernardelli, Giuseppina; Mari, Daniela (Frontiers in Psychology, 2018)
In the last few decades, the relationship between physical conditions and mental health has increasingly attracted the interest of researchers and professionals across disciplines. This relationship is especially relevant in old age, as the challenges posed by aging at various levels represent crucial concerns for policy makers. Due to the remarkable increase in life expectancy across countries, sustainable prevention strategies are needed to help individuals preserve psychophysical well-being in old age. In particular, the regular practice of a moderately intense physical activity is recommended by the World Health Organization to enhance balance, prevent falls, strengthen muscles, and promote psychophysical well-being. Daily physical exercise represents a beneficial and low-cost strategy, easily accessible to the general population and potentially customizable to specific needs through brief training programs. Based on these premises, the present research aimed at longitudinally evaluating mental well-being among 58 Italian people aged 67-85, who were involved in two Adapted Physical Activity (APA) training programs. Inclusion criteria for participation comprised high autonomy levels in daily activities, no cognitive impairment, sedentary habits or only occasional performance of moderate physical activity. Based on physical and functional assessment, 39 participants joined a program of adapted motor activity (PoliFit; Study 1), while 19 participants attended a variant program specifically designed for people with osteoporosis (OsteoFit; Study 2). Well-being dimensions were assessed through the the Mental Health Continuum-Short Form, the Emotion Regulation Questionnaire and the Satisfaction with Life Scale,. Physical functioning were evaluated before and after the programs through the Short Physical Performance Battery and the Handgrip Dynamometer Jamar Test. Findings highlighted that, besides physical benefits, participants reported significantly more adaptive emotion regulation strategies after both training programs; in addition, participants attending OsteoFit reported significantly higher levels of emotional well-being. Results suggest the potential of moderate physical activity in promoting mental health, emphasizing the additional role of training programs as cost-effective opportunities for elderly people to socialize and improve emotional functioning. Overall, the findings support the view of old age as a stage of competence development and adaptive adjustment, rather than a phase of mere psychophysical decline.